2019
DOI: 10.1098/rsos.190504
|View full text |Cite
|
Sign up to set email alerts
|

Poly(butylene succinate- co -salicylic acid) copolymers and their effect on promoting plant growth

Abstract: Biodegradable random copolymers were successfully synthesized by melt polycondensation of poly(butylene succinate) (PBS) and salicylic acid (SA). The obtained copolymers were characterized by proton nuclear magnetic resonance spectroscopy. The effect of different SA contents on the properties of copolymers was investigated by universal testing machine, thermogravimetric analyser, differential scanning calorimetry and X-ray diffraction analysis. The results showed that the copolymers with 0.5% SA contents exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
8
2
Order By: Relevance
“…The copolymerization of PBS with salicylic acid was studied as an attempt to produce polymer films with potential applications in agricultural applications. Enzymatic degrada-tion assays carried out in the presence of Candida antarctica lipase B (CALB) showed very low degradation after 20 days (~1.5 wt% for neat PBS); however, the addition of salicylic acid increased this value up to ~3.5 wt% [158].…”
Section: Pbs-based Copolymers: Hydrolytic and Enzymatic Degradationmentioning
confidence: 99%
“…The copolymerization of PBS with salicylic acid was studied as an attempt to produce polymer films with potential applications in agricultural applications. Enzymatic degrada-tion assays carried out in the presence of Candida antarctica lipase B (CALB) showed very low degradation after 20 days (~1.5 wt% for neat PBS); however, the addition of salicylic acid increased this value up to ~3.5 wt% [158].…”
Section: Pbs-based Copolymers: Hydrolytic and Enzymatic Degradationmentioning
confidence: 99%
“…Instead of only focusing on the degradation mechanisms and coating loss, they evaluated how the degradation of the polymer promoted the growth of a Chinese cabbage. 69 The authors indicated that the inclusion of salicylic acid (which can lead to improved plant resistance to pathogens) 70 increased the rate of degradation by the lipase compared to poly(butylene succinate) without salicylic acid; the root cause of this effect was purported to be increased crystallinity. However, we need to continue to make comparisons between hydrolases on comparable polymer blends so that we obtain more quantitative measurements of activity and mechanisms as more recombinant and native hydrolases are isolated.…”
Section: Aliphatic Polymers With Succinate and Adipatementioning
confidence: 99%
“…A hyperbranched polyester (HBPE) based on SA increased twice in fluorescence intensity compared to the acyl chloride terminated HBPE and proved more effective than standard antibacterial drugs such as ciprofloxacin and clotrimazole in inhibiting bacteria and fungi . The copolymer prepared by using butylene succinate (PBS) and SA as raw materials not only significantly enhanced the degradation performance of PBS but also released SA continuously during the degradation process to promote the growth of vegetables . Therefore, SA and PSA exhibit robust fluorescence properties due to the fluorescent group in the molecule structure and afford a broad application prospect.…”
Section: Introductionmentioning
confidence: 99%